ENGINEERING PREPARATION OF THE SOIL BASE FOR THE FOUNDATIONS OF THE CONSTRUCTIONS OF THE DERHACHI SOLID WASTE LANDFILL - Strizhelchyk, H.; Bondarenko, O.; Khrapatova, I.; Palchenko, O.; Liapin, O. (Municipal economy of cities. Series: «Economy science», 2024)
After conducting engineering and geological investigations, it became necessary to provide scientific support for construction in terms of engineering preparation of the soil base for the foundations of the structures due to extreme unsustainability in the plan and depth of the rocks. Such engineering-geological conditions significantly impact the choice of foundation structures and the justification of measures to reduce or eliminate the negative effect on the environment and the development of dangerous geological processes and phenomena. We thoroughly studied the deformation and strength properties of the supporting soil layers and developed recommendations for their engineering preparation and improvement of the indicators. Bulk soil is present in local depressions: construction debris, sand, and compacted loam. Based on the analysis of physical and mechanical properties, we could conclude that this soil cannot be used as a soil base for the foundations of buildings due to its loose composition and enrichment with organic substances and must be completely replaced during the production of earthworks. They can be used as a basis for laying engineering networks. After excavation pits for individual columns, before setting up the preparation, it is necessary to carefully inspect the soil foundation to ensure that it is the same engineering and geological element specified in the project. The soil base of the foundations is redeposited subsidence loess loams, which have mostly lost their subsidence properties, but local inclusions with subsidence properties have remained in the thickness of these soils. If there are lenses of soils in the soil base with indicators of physical and mechanical characteristics that are lower than those adopted in the project and that have a thickness of less than one meter, they should be removed and replaced with sand or sand-crushed soil with layer-by-layer compaction and compaction quality control. Doing so will create the same soil conditions for the building foundation. The performed scientific and technical support of the construction made it possible to choose a method of technical soil reclamation—partial replacement of weak soils with sand and crushed stone, which, after layer-by-layer compaction, can withstand a significant load and stability under vibrational influences.